Self-efficacy with self-management among patients with diabetes mellitus - Trina Kurniawati; Eka Budiarto; Nur Intan Kusuma (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Poorly controlled diabetes mellitus increases the risk of serious complications, making effective self-care management essential. Self-care behaviors are influenced by multiple factors, with self-efficacy recognized as a key psychological component affecting an individual’s capacity to manage chronic illnesses such as diabetes. Purpose: To examine the association between self-efficacy and self-care management among patients with diabetes mellitus. Method: A correlational study with a cross-sectional design was conducted using purposive sampling. A total of 36 respondents were included. Data were collected using the Diabetes Management Self-Efficacy Scale (DMSES) and the Summary of Diabetes Self-Care Activities (SDSCA). Statistical analysis was performed using the Pearson correlation test. Results: The analysis revealed a statistically significant relationship between self-efficacy and self-care management in patients with diabetes mellitus (p = 0.014). Conclusion: Lower levels of self-efficacy among individuals with diabetes mellitus significantly hinder the implementation of effective self-care management. Insufficient confidence in managing their condition leads patients to act inconsistently with recommended health behaviors. Consequently, strengthening self-efficacy and motivation is essential to improve adherence to diabetes management.